Pengaruh Leverage, Likuiditas dan Profitabilitas terhadap Risiko Sistematis pada Perusahaan Manufaktur Subsektor Food and Beverage - Selfi Anggraini; Risal Rinofah; Pristin Prima Sari (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study is to test and explain the effect of leverage, liquidity and profitability on systematic risks in food and beverage subsector manufacturing companies listed on the IDX in the 2018-2021 period. The population of this study is 72 companies manufacturing in the food and beverage subsector for the 2018-2021 period. Sampling in this study used purposive sampling technique, namely sampling with certain criteria and obtained as many as 46 companies for 4 years, so that 184 observations were obtained. This study used the multiple regression analysis method with the help of the spss program version 20. The independent variables in this study are leverage, liquidity and profitability, as well as dependent variables, namely systematic risk. The results of this study show that the partial influence of leverage and liquidity variables has a positive and insignificant impact on systematic risk, while the profitability variable has a negative and significant impact on systematic risk. Meanwhile, variable leverage, liquidity, and profitability simultaneously have a significant effect on systematic risk.